The Transformation of Religious Identity in the Public Sphere: A Phenomenological Study of the Hijrah Movement among Urban Millennials - Abdullah Safei; Agus Handoko (Al-madinah: Journal of Islamic Civilization, 2026)
The phenomenon of the hijrah movement among urban millennials has transformed the landscape of religiosity in the urban public sphere. This study aims to analyze the transformation of religious identity among urban millennials and examine how they negotiate that identity within the context of urban modernity. Employing a qualitative method with Alfred Schutz's phenomenological approach, this research explores the subjective experiences of hijrah participants in major Indonesian cities (Jakarta and Bandung) during the period from January to December 2025. Data were collected through offline participant observation within hijrah communities, in-depth interviews with six key informants, and netnographic research conducted on Instagram and TikTok. The findings reveal three major themes. First, the transformation of religious identity is driven by because-motives rooted in social anomie and in-order-to motives oriented toward the search for moral certainty. Second, religious identity has shifted from the private to the public sphere through forms of religious aesthetics that are integrated into the lifestyle of the Muslim middle class. Third, the netnographic findings confirm that digital technology has fostered the emergence of digital piety, in which the validation of religious devotion increasingly takes place within virtual spaces. This study concludes that the hijrah movement among urban millennials represents a dynamic adaptation of Muslim identity, giving rise to a new subculture that integrates religious orthodoxy with capitalist modernity while simultaneously reinforcing the process of desecularization in the urban public sphere.